Fisheries' Property Regimes and Environmental Outcomes: A Realist Synthesis Review - McLain, R.; Lawry, S.; Ojanen, M. (Elsevier, 2018)
Our paper describes the application of a realist approach to synthesizing evidence from 31 articles examining the environmental outcomes of marine protected areas governed under different types of property regimes. The development of resource tenure interventions that promote sustainable management practices has been challenged by the difficulties of determining how contextual factors affect environmental outcomes given the complexity of socio-ecological systems. Realist synthesis is a promising evidence review technique for identifying the mechanisms that influence policy intervention outcomes in complex systems. Through a combination of inductive and deductive analysis of the links between context, mechanisms, and outcomes, realist synthesis can help clarify when, how, where, and why property regime interventions are likely to result in positive environmental outcomes. Our study revealed the importance of disaggregating property regimes into sub-categories, rather than treating them as homogenous categories. More importantly, use of a realist synthesis approach allowed us to gain a deeper understanding of the ways in which three mechanisms—perceptions of legitimacy, perceptions of the likelihood of benefits, and perceptions of enforcement capacity—interact under different socio-ecological contexts to trigger behavioral changes that affect environmental conditions. The approach revealed the multi-faceted and interactive nature of perceptions of legitimacy, in which legal legitimacy, social acceptability, and ecological credibility combined to create robust legitimacy. The existence of robust legitimacy in turn appeared to be an important contributor to the success of regulatory systems reliant on voluntary compliance. Our study contributes to the field of natural resources governance by demonstrating the utility of a systematic review method which has received little attention by property scholars but which has promise to clarify understanding of how complex systems work. Our study also highlights that achieving long-term sustainability requires paying greater attention to the mechanisms that support or undermine people's willingness to voluntarily engage in conservation behaviors.